Behaviour Study of Abutment Foundation Pile on Lightweight Embankment Oprit (Case Study: Kali Otek Bridge – Lamongan North Ring Road Construction Package Section 2) - Nila Wahyu Pertiwi; Ria Asih Aryani Soemitro; Trihanyndio Rendy Satrya; Sifa’ Udukha (Journal of Infrastructure & Facility Asset Management, 2025)
The Kali Otek Bridge is in the Lamongan North Ring Road Development Package Section 2 with a bridge span length of 40.8m. The boring test results show that the subgrade is included in the very soft soil classification to a depth of >15 meters. The existing condition is a pond area that can be inundated with water reaching a height of 1 meter, thus affecting the occurrence of land subsidence and stability of the bridge abutment foundation pillars. The existence of embankment construction can also cause subsidence on the subgrade.In this research, soil settlement and stability analysis of lightweight foam mortar embankment has been carried out by varying the percentage of the height of the existing embankment and the foam mortar. In addition, it also analyzes the effect of using lightweight embankment, both as a whole and its variations on the stability of bridge abutment foundation piles, both with and without Prefabricated Vertical Drain (PVD).The analysis showed that the use of foam mortar reduced the subgrade settlement by 61.2% with a longer time of 18.5%. The smallest settlement and lateral deflection was at 100% foam mortar backfill variation with consolidation time of 190 days. The greater the percentage of foam mortar height, the smaller the settlement as the factor of safety increases. Thus, the use of foam mortar can be an alternative embankment for bridge oprites on soft soil.